Constructing Lipoparticles Capable of Endothelial Cell-Derived Exosome-Mediated Delivery of Anti-miR-33a-5p to Cultured Macrophages - Jing Echesabal-Chen; Kun Huang; Lucia Vojtech; Olanrewaju Oladosu; Ikechukwu Esobi; Rakesh Sachdeva; Naren Vyavahare; Hanjoong Jo; Alexis Stamatikos (Current Issues in Molecular Biology, 2023)
Atherosclerosis is driven by intimal arterial macrophages accumulating cholesterol. Atherosclerosis also predominantly occurs in areas consisting of proinflammatory arterial endothelial cells. At time of writing, there are no available clinical treatments that precisely remove excess cholesterol from lipid-laden intimal arterial macrophages. Delivery of anti-miR-33a-5p to macrophages has been shown to increase apoAI-mediated cholesterol efflux via ABCA1 upregulation but delivering transgenes to intimal arterial macrophages is challenging due to endothelial cell barrier integrity. In this study, we aimed to test whether lipoparticles targeting proinflammatory endothelial cells can participate in endothelial cell-derived exosome exploitation to facilitate exosome-mediated transgene delivery to macrophages. We constructed lipoparticles that precisely target the proinflammatory endothelium and contain a plasmid that expresses XMOTIF-tagged anti-miR-33a-5p (LP-pXMoAntimiR33a5p), as XMOTIF-tagged small RNA demonstrates the capacity to be selectively shuttled into exosomes. The cultured cells used in our study were immortalized mouse aortic endothelial cells (iMAECs) and RAW 264.7 macrophages. From our results, we observed a significant decrease in miR-33a-5p expression in macrophages treated with exosomes released basolaterally by LPS-challenged iMAECs incubated with LP-pXMoAntimiR33a5p when compared to control macrophages. This decrease in miR-33a-5p expression in the treated macrophages caused ABCA1 upregulation as determined by a significant increase in ABCA1 protein expression in the treated macrophages when compared to the macrophage control group. The increase in ABCA1 protein also simulated ABCA1-dependent cholesterol efflux in treated macrophages—as we observed a significant increase in apoAI-mediated cholesterol efflux—when compared to the control group of macrophages. Based on these findings, strategies that involve combining proinflammatory-targeting lipoparticles and exploitation of endothelial cell-derived exosomes appear to be promising approaches for delivering atheroprotective transgenes to lipid-laden arterial intimal macrophages.